MODERN PEDAGOGICAL APPROACHES IN TEACHING SPECIALIZED SUBJECTS FOR GRADUATES OF THE HIGHER NURSING FACULTY (International journal of medical sciences, 2026)
This scientific article analyzes modern pedagogical approaches used in teaching specialized subjects by graduates of the Higher Nursing Faculty. The study examines the role of competency-based education, practice-oriented training, and simulation technologies in the educational process. The results demonstrate that the development of pedagogical and professional competencies of specialized subject teachers contributes to improving the quality of education.